Online student profile management system - Malgireddy, Greeshma (Kansas State University, 2010)
All the students who are enrolled in Computing and Information Sciences (CIS) major in Kansas State University are required to submit their Program of Study (POS) which they manually do by filling in all the necessary details and submit the form to the department. The main objective of this project is to develop an online submission of program of study. The online student profile management system is a web-based application that provides students of CIS major to submit their program of study in an easy and efficient manner. This application mainly allows the students to enter their personal information (viz., contact information, previous education) and to choose core as well as non-core courses of their choice. In addition the faculty of CIS department can also log on to the application and view the POS of the students by entering their wildcat ID. The primary focus is to get familiar with .NET framework and to code in C#.NET. This in turn uses MS SQL server 2005 as database for storing and retrieving of data. This project is implemented using C#.NET on Microsoft visual studio 2005.
Keywords: C#.Net; POS; Computer Science (0984)